2013
DOI: 10.1590/s1806-83242013000500004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the interposition of ceramic spacers on the degree of conversion and the hardness of resin cements

Abstract: This study evaluated: I) the effect of photo-activation through ceramics on the degree of conversion (DC) and on the Knoop hardness (KHN) of light-and dual-cured resin cements; and II) two different protocols for obtaining the spectra of uncured materials, to determine the DC of a dual-cured resin cement. Thin films of cements were photoactivated through ceramics [feldspathic porcelain (FP); lithium disilicate glass-ceramics of low translucency (e.max-LT), medium opacity (e.max-MO) and high translucency (e.max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
6
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 22 publications
4
68
6
6
Order By: Relevance
“…Although the resin composite evaluated in the present study is indicated for the cementation of ceramic restorations, other light-activated materials (i.e. the so called "veneer cements") have been indicated for the cementation of thin veneers 10 and also have shown good DC results when light-activated through ceramic materials [13][14] . As seen in Table 2, the similar results for DC in most groups indicate that the shade and thickness of the evaluated interposed ceramic veneers did not influence the polymerization of the flowable resin composite.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although the resin composite evaluated in the present study is indicated for the cementation of ceramic restorations, other light-activated materials (i.e. the so called "veneer cements") have been indicated for the cementation of thin veneers 10 and also have shown good DC results when light-activated through ceramic materials [13][14] . As seen in Table 2, the similar results for DC in most groups indicate that the shade and thickness of the evaluated interposed ceramic veneers did not influence the polymerization of the flowable resin composite.…”
Section: Discussionmentioning
confidence: 98%
“…More opaque ceramics tend to absorb more light, which would decrease the DC of light-cured resin-based materials 20 . It has been reported that the DC of resin-based materials may change considerably as function of the type and opacity of the interposing ceramics [13][14] . Another aspect to be addressed is that one single shade of flowable resin composite was evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,4 The hardness of DCRCs was investigated, and it was reported that the thickness as well as the shade of the resin or ceramic inlays could affect the hardness of the resin cement. 5,6 Esthetics in the posterior region are not as critical as in the anterior region, and the shade guides of many direct resin composite systems recommend using a single dentin layer or dentin and enamel layers for posterior restorations. Some indirect resin composite systems are composed of dentin, enamel, and translucent layers, and manufacturers recommend Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%